Intractable conflicts : socio-psychological foundations and dynamics - Bar-Tal, Daniel (Cambridge University Press, 2013)
"This book provides a comprehensive, interdisciplinary, original, and holistic analysis of the socio-psychological foundations and dynamics of intractable conflicts and their resolution"--